Snack Business Development Strategy Using the Canvas Model Business Approach at UD Mentari Jaya Putra, Tanggul District, Jember District - Tarigan, Rallyanta (PT Aksara Indo Rajawali, 2025)
Business competition is currently increasing, companies must improve their business capabilities so that their businesses can develop and compete with other companies. Therefore, companies must have a strategy so that their business continues to run and develop. Research on